Heterotrimeric G-proteins and their role in opioid receptor function - Fábián, Gabriella (Acta Biologica Szegediensis, 2001)
Heterotrimeric G-proteins are signal transducers of heptahelical receptors. They consist of a and bg subunits, both capable of interacting with several different effectors. Specific domains in their structures enable them to connect different intracellular signaling cascades, such as the adenylyl cyclase, phosphoinositol-bisphosphate or MAP kinase pathways. Their activity is synchronized by several components, one of them being a new protein family termed RGS (regulators of G-protein signaling). Members of this family inhibit the G-protein function. The intracellular localization of G-proteins indicates their role in plasma membrane-independent processes. Opioid receptors transmit their signals mainly via Gi/o proteins. Although the heterogeneity of opioid ligands (peptides and alkaloids) and their receptors (m, d, k and suggested subtypes in these classes) reveals a complicated picture, their unique characteristic of a high dependence capacity can not be explained without the analysis of the G-protein function.